2018
DOI: 10.2478/rela-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Production Accuracy of L2 Vowels: Phonological Parsimony and Phonetic Flexibility

Abstract: Ultimate attainment in foreign-language sound learning is addressed via vowel production accuracy in English spoken by advanced Czech EFL learners. English FLEECE-KIT, DRESS-TRAP, and GOOSE-FOOT contrasts are examined in terms of length, height, and backness. Our data show that, while being constrained by phonemic category assimilation (new vowel height distinctions are not created), the learners' interlanguage combines phonological parsimony (reusing L1 length feature to contrast L2 vowels) with phonetic flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(49 reference statements)
2
4
1
Order By: Relevance
“…Šimáčková found that Czech learners rely predominantly on duration when deciding between the English /ae/ and /e/, and that their production of the two vowels spectrally overlap. Similar results were obtained by Šimáčková and Podlipský (2018): even highly proficient Czech speakers of English used duration to contrast the two vowels, with vowel height being less reliable. Šturm and Skarnitzl (2011) studied perceptual aspects of the vowel /ae/ by two groups of listeners: students who had been instructed in the phonetics and phonology of English and naïve students with no such formal instruction.…”
Section: Vowels In Czech Englishsupporting
confidence: 73%
“…Šimáčková found that Czech learners rely predominantly on duration when deciding between the English /ae/ and /e/, and that their production of the two vowels spectrally overlap. Similar results were obtained by Šimáčková and Podlipský (2018): even highly proficient Czech speakers of English used duration to contrast the two vowels, with vowel height being less reliable. Šturm and Skarnitzl (2011) studied perceptual aspects of the vowel /ae/ by two groups of listeners: students who had been instructed in the phonetics and phonology of English and naïve students with no such formal instruction.…”
Section: Vowels In Czech Englishsupporting
confidence: 73%
“…However, the same production data showed that /ae/ and /ɛ/ are easily confused in these EFL learners' speech, and that compared to the other English monophthongs, both /ae/ and /ɛ/ display increased within-speaker variation, as well as substitutions between each other in pronunciation of individual lexical items. In Šimáčková and Podlipský (2018), learners' productions of /ae/ showed little lowering or retraction as compared with /ɛ/. In this respect, the production data do not match the current vowel identification data elicited in Pilot 1.…”
Section: Pilot 1 -With a Final Session Using Noise-maskingcontrasting
confidence: 70%
“…The logistic regression model also allows us to assess how accurately the learners identified each of the eleven vowel categories. Identification accuracy of the individual vowel monophthongs was measured against the KIT vowel as the reference category, since it was earlier shown that /ɪ/ is the most accurately produced English vowel in speech of Czech EFL learners (Šimáčková and Podlipský 2018), and also since it had the highest identification accuracy in the present results: as seen in Table 2, all other vowel categories had significantly lower likelihood of correct answers. In Table 2 the vowel categories are ordered from those with the greatest negative difference from KIT (the vowel TRAP) to the lowest (the vowel FLEECE).…”
Section: Pilot 1 -With a Final Session Using Noise-maskingmentioning
confidence: 61%
See 2 more Smart Citations